SARS‐CoV‐2 viral spike G614 mutation exhibits higher case fatality rate. Issue 8 (3rd June 2020) - Becerra‐Flores, Manuel; Cardozo, Timothy
Abstract: Aim: The COVID‐19 pandemic is caused by infection with the SARS‐CoV‐2 virus. The major mutation detected to date in the SARS‐CoV‐2 viral envelope spike protein, which is responsible for virus attachment to the host and is also the main target for host antibodies, is a mutation of an aspartate (D) at position 614 found frequently in Chinese strains to a glycine (G). We sought to infer health impact of this mutation. Result: Increased case fatality rate correlated strongly with the proportion of viruses bearing G614 on a country by country basis. The amino acid at position 614 occurs at an internal protein interface of the viral spike, and the presence of G at this position was calculated to destabilise a specific conformation of the viral spike, within which the key host receptor binding site is more accessible. Conclusion: These results imply that G614 is a more pathogenic strain of SARS‐CoV‐2, which may influence vaccine design. The prevalence of this form of the virus should also be included in epidemiologic models predicting the COVID‐19 health burden and fatality over time in specific regions. Physicians should be aware of this characteristic of the virus to anticipate the clinical course of infection.